Assessing Support Requirements for Multidisciplinary Team Meetings - KANE, BRIDGET (IEEE, 2010)
This paper profiles multidisciplinary team activity (MDT) in a typical teaching hospital setting and reports on a survey conducted among the teams to establish the information needs and constraints which affect their interaction. Support for pre-meeting work and post-meeting responsibilities is considered important in enabling the interaction at team meetings to be effective. Acoustics in the meeting room have higher priority over visual displays, although both `hearing the discussion? and `seeing images and colleagues? is important at meetings. Issues of time include scheduling and timing and are difficult to manage, particularly when individual roles belong to several MDTs and span more than one hospital. The potential is identified for automatic processing of some decisions by simple algorithm, which potentially will allow for more time at meetings to discuss complex patient cases in more detail.
The 23RD IEEE International Symposium on Computer-Based Medical Systems (CBMS 2010)
PUBLISHED
Perth, Western Australia
Keywords: Multidisciplinary team; collaborative work; CSCW; Health Sciences; Cancer; Smart & Sustainable Planet